ANALYTICAL STUDY OF ADJUSTMENT IN BTC AND SPECIAL BTC TRAINED TEACHERS WORKING AT PREPARATORY STAGE - Singh, Gajendra; Gola, Rajkumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
It is only through education that any person’s all-round development takes place, he develops the society and the country by becoming a useful member of the society. Primary education is the foundation stone of making a child civilized, well-cultured, without strengthening it, the desired society cannot be achieved, therefore, there is always pressure on the leaders of the society and the country, how to organize this level of education so that the expected results can be achieved and the nursery being prepared for the needs of the society and the country can be given the right direction so that they can become a capable member for the society and the country and can make their important contribution in the upliftment of the country and human society. For all this, it is necessary that such arrangements be made according to the changing times so that they are ready to receive education, they receive education with entertainment, they feel good in coming to school and staying there, this can happen only when the things prevalent in the society are available in the school so that the environment there does not seem different to them which is boring with their lifestyle. Rousseau says, ’We cannot learn anything from such a student whom we hate. Children should not only come to school but also stay there regularly till school hours and happily absorb the information given on various subjects in a better way. Various commissions have emphasized from time to time that the stay of children in school should be increased. Various efforts have been made for all this. To make teaching interesting and comprehensible, emphasis has been laid on the adjustment of teachers in this field. Key words: Preparatory stage, job satisfaction, influence, teacher. Introduction: - Education is the basic foundation of human development. It is through this that the development of individuals, society and nation takes place. In fact, it helps a person to achieve all that he is capable of and aspires for. It is difficult to limit its functions. We all are aware of the fact that mental development is directly related to thoughts and thoughts to language, the development of language and thoughts is possible only through education. Education develops many mental powers such as memory, observation, imagination, logic and discretion. According to Kant (Saxena and Chaturvedi, 2004, p. 10), “Education is the development of that perfection of a person which he is capable of.” Education makes a person optimistic by freeing him from despair, and self-confident by freeing him from inferiority, making him worth living. “Education is that source of knowledge, through which the darkness of ignorance is destroyed automatically.” It is said that education removes inertia and makes life excellent. Education acts as a life-giver in life. Only after acquiring education, a person remains engaged in the perfection of life. Education is one of the most important needs of life. The process of education involves three elements. Teacher, learner and curriculum. The teacher tries to develop the desired qualities in the students through the curriculum. In the absence of capable, committed and dedicated teachers, even the best education system is bound to fail. Perhaps that is why it seems difficult, if not impossible, to imagine education without a teacher. In the Vedic period, there were Rishis, Gurus and teachers. In the society, the Guru had the status of God. But now the conditions have changed, however, the importance of the teacher in the education system cannot be denied. Even today, he is the source of knowledge for the child, through which the child acquires not only spiritual but also worldly and practical knowledge.